PERMASALAHAN AKSESIBILITAS BAGI PENYANDANG CACAT DI KOTA PALEMBANG, PROVINS! SUMATERA SELATAN - Ike Atikah Azhuri (Sosio Informa, 2005)
(The Accesibility Problem for People with Disabilities in Palembang, South Sumatera) - The essential problem discussed in this paper is accesesibility of infras tructures and equipments for the disable in public area such as in buildings, streets, parks, cemeteries, public transportations. This accessibility is provided for the disabled people to have their activities in public area easrly. These efforts are based on the law Number 4, year 1997 concerning the welfare of People with Disabilities. It is necessary for the government and communities to provide the medium accessibility of infrastructures and equipments amenity for disabled. The objective of the research is identifiying medium accessibility infrastructures in building and its surrounding to make the d isabled do their activities easily. Since the application of this law in the reality the providing of that accessibility is still minimum and have not yet get properly standarized according to min istrial decree of public work number 468/KPTS/1998 about technical conditions of accessibilities in public buildings and its environment. The application of minis trial decree of public work, on the provision of accessibility have not been arranged in the provincial regulation, so the social iza tion of that accessibility provision for the disables is less effective. It is because of limiting power between the governments in the provincies, regencies, etc. as well as the often rotation of selfs for them in government institutions resulted the lack of experience.